Hubungan Pengetahuan, Dukungan Keluarga, dan Sikap Ibu Pra-nikah dengan Pelaksanaan Imunisasi Tetanus Toksoid (TT Catin) - Nisa, Mahdiyatun; Sugesti, Retno; Wulandari, Ratna (MPI Press, 2024)
Introduction: A mandatory program based on the cooperation Ministry of Health and the Ministry of Religion is the desired partner Mary must follow a test health premarital TT immunization. Objectives: To find out the relationship between knowledge, family support, and attitudes of premarital mothers with the implementation of Tetanus Toxoid immunization (TT Catin) at the UPT Puskesmas Petir in 2022. Method: Type study descriptive analytics with the use method quantitative cross-sectional. Sample as many as 67 respondents using the technique of probability sampling that is sample random sampling. The instrument study uses a questionnaire. Data analysis using analysis univariate and bivariate with the chi-square test. Result: The results showed the relationship between knowledge (p = 0.000), family support (p = 0.001), and attitudes (p = 0.002) then family support (p = 0.002), and attitudes (p = 0.001) of premarital mothers with the implementation of Tetanus Toxoid immunization (TT catin) at the UPT Puskesmas Petir in 2022. Conclusion: Knowledge, family support, and attitudes have a significant effect on the implementation of TT Catin immunization.